The City as Escape Room: Place, Participation, Meaning, and Affect - Roy Hanney (Acta Universitatis Sapientiae: Film and Media Studies)
Through the lens of ecologies of belonging, The City as Escape Room transfers a simple and commonly held understanding of the escape room into a metaphor that reveals a complex layering of place, participation, and affect in meaning-making for transmedia storytellers. It situates the city as a play space where community participation, meaning-making, and co-creation are interwoven as meaningful story experiences. By mirroring the practice of urban foraging, the discussion explores transmedia storytelling as a form of sympoiesis that brings into being a shared memory, a becoming-with the city for the community that resides within. Avoiding the common placemaking tropes associated with public sector marketing and economic (re)generation, city-wide transmedia storytelling is instead considered a form of speculative fabulation that can defamiliarize the familiar and generate affective story experiences. The offering of a case study that contrasts commercial and community-driven transmedia experiences further illuminates how immersive experience design can take hold of a city as a play space and render it as a meaningful story experience.